Orai1/CRACM1 overexpression suppresses cell proliferation via attenuation of the store-operated calcium influx-mediated signalling pathway in A549 lung cancer cells - Hou, Ming-Feng; Kuo, Ho-Chang; Li, Jih-Heng; Wang, Yu-Shiuan; Chang, Chen-Chia; Chen, Ku-Chung; Chen, Wei-Chiao; Chiu, Chien-Chih; Yang, Shengyu; Chang, Wei-Chiao (Biochimica et biophysica acta, 2011)
Orai1/CRACM1 is a principal component of the store-operated calcium channels. Store-operated calcium influx is highly correlated with inflammatory reactions, immunological regulation, and cell proliferation. Epidermal growth factor (EGF), which plays an important role in the regulation of cell proliferation, can activate store-operated calcium channels. However, the consequences of Orai1/CRACM1 overexpression in EGF-mediated lung cancer cells growth are not known. To investigate the role of Orai1/CRACM1 in EGF-mediated lung cancer cell proliferation, Orai1/CRACM1 plasmids were transfected into cells by lipofection. A cell proliferation assay, immunofluorescence staining, flow cytometry, and real-time polymerase chain reaction were employed to monitor cell proliferation. The calcium influx signals were investigated using a fluorescent-based calcium assay. Transfection of Orai1/CRACM1 plasmids resulted in the inhibition of EGF-mediated cell proliferation. ERK1/2 and Akt phosphorylation were inhibited by Orai1/CRACM1 overexpression. Expression of the cell cycle modulator p21 was induced in the Orai1/CRACM1-overexpressing cells, whereas the expression of cyclin D3 was reduced. Flow cytometry revealed that overexpression of Orai1/CRACM1 resulted in G0/G1 cell cycle arrest. Importantly, Orai1/CRACM1 overexpression significantly attenuated EGF-mediated store-operated calcium influx. In addition, application of 2-APB, a store-operated calcium channel inhibitor, resulted in the inhibition of EGF-mediated cancer cell proliferation. We conclude that Orai1/CRACM1 overexpression attenuates store-operated Ca 2+ influx that in turn blocks EGF-mediated proliferative signaling and drives cell cycle arrest. ► Orai1/CRACM1 overexpression resulted in the reduction of cell proliferation ► Phosphorylation of ERK1/2 and Akt is blocked by Orai1/CRACM1 overexpression. ► Orai1/CRACM1 overexpression resulted in a cell cycle G0/G1 phase arrest. ► Store-operated calcium inhibitors influenced cell proliferation.